Impact of students’ self-regulation and mindfulness on academic self-efficacy; the mediation effect of mental well-being - Mariyam Shareefa; Visal Moosa; Khaulath Saeed; Visama Hassan; Muhamed Kashif (Cogent Education)
This study explored how academic self-efficacy was affected by self-regulation, mindfulness and their indirect impacts through mental well-being among higher education students in the Maldives. A survey questionnaire adapted from various sources was conducted to 333 students selected from various higher education institutions. The results showed that students’ academic self-efficacy is positively impacted by both self-regulation and mindfulness. Furthermore, mental well-being was found to play a mediating role in the relationship between both self-regulation and mindfulness with academic self-efficacy, emphasizing the critical role that mental health plays in promoting academic achievement. These results advance our knowledge of the relationship between mental health and academic success, and point to the potential advantages of self-regulation and mindfulness-promoting therapies for enhancing students’ wellbeing and academic self-efficacy in higher education.